PERAN GURU PEMBINA DALAM INTERAKSI SISWA BERWIRAUSAHA ONLINE SHOP DI SMA NEGERI 1 PEMANGKAT - Laras Dwi Hatmanti; Rustiyarso Rustiyarso; Supriadi Supriadi (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine the role of the choach teacher in online shop interaction at SMA Negeri 1 Pemangkat. The research method used was descriptive in the form of qualitative research. The data sources in this study were the guidance teachers and students. The scope of the research includes associative interaction patterns in the form of cooperation and bargaining. Data collection techniqued with observation guides, interviews, and documentation studies. The results of the research prove that: The guidance teacher plays a very good role in directing students to entrepreneurship online, this can be seen from the cooperation directed by the guidance teacher in dividing students into groups, the duties and responsibilities of each member, and always guiding student entrepreneur groups. Bargaining which is directed by the guidance teacher can be seen from the marketing of students on social media and controlling the buying and selling prices of students through social media WhatsApp and Facebook which are going very well.Keywords : The role of the guidance teacher, Entrepreneurial interactions, online shop